Medical professions in Poland – selected legal aspects - MiaskowsKa-Daszkiewicz, Katarzyna (Polish Journal of Public Health, 2018)
This article is a voice in the discussion of legal problems related to understanding the concept of a medical profession. The considerations were divided into three main parts. In the first one, the concept of “medical profession” was reconstructed and problems in the classification of particular professions to the category of medical professions were pointed out. Not every medical profession is characterized by the quality of public trust, although due to the good that medical professions are dealing with, such a state would most likely be the most desired one. In the second part of the text, based on the jurisprudence of the Constitutional Tribunal, the features determining the recognition that a given profession is a profession of public trust were indicated. These remarks were related to medical professions. The content of the third part is a consequence of the fact that it is difficult to precisely establish a catalog of medical professions. The practical significance of the lack of systemic solutions in defining a medical profession is given in the example of tax law, in the scope of the exemption from the Goods and Services Tax